Data gathering system for apparel industry - Ferreira, Tânia (2019)
This paper describes a project that is being developed at Escola Superior de Tecnologia - Instituto Politécnico de Castelo Branco – Portugal. It consists of a prototype for a real time data pick up system, using the Controller Area Network (CAN) bus. The goal is the gathering of data contained in bar code labels that are coupled to cloths pieces in an apparel factory during the production process.